Development of smart nursing homes using systems engineering methodologies in industry 4.0. Issue 4 (20th April 2020) - Cui, Fengming; Ma, Liang; Hou, Guofeng; Pang, Zhibo; Hou, Yonghong; Li, Lefei
ABSTRACT: As aged population grows and health informatics advances dramatically, smart nursing homes equipped with electronic devices and intelligent systems turn into a hotspot. In this paper we propose an iterative and life-cycle development process based on the Vee model in Systems Engineering. Some tools like the house of quality matrix are introduced to continuously identify, allocate and refine requirements from elder residents, engineers, and other stakeholders. The development model proposed highlights the synchronization development of cyber phsical system with the smart nursing home. Furthermore, a agent-based simulation is implemented to illustrate feasibility and applicability of our work.